Gaya Bahasa Dalam Puisi Tu’āẓmnī Żanbī Karya Imam Syafi’i: Analisis Stilistika - Kurniawan, Raden Muhammad Ardiansyah; Sukarno, Berliana Sukma Tri; Ritonga, Ridwan; Ramadhani, Gita Fitri (Universitas Muhammadiyah Gorontalo, 2024)
This study aims to reveal what kind of language Imam Syafi'i uses in his poem, Tu’āẓimnī Ẓanbī. In looking for aspects of beauty and meaning, this study uses the theory of stilistics presented by Syihabuddin Qalyubi. According to him, the level of stilistic analysis includes five aspects of study, namely phonology, morphology, syntax, semantics, and imagery. This research uses descriptive method with qualitative analysis. The source of this research data is the poem of Imam Syafi'i, Tu’āẓimnī Ẓanbī. The results showed the existence of a distinctive language style used by Syafi'i imams, thus causing a beautiful meaning effect. Five aspects of stylistic analysis in this poem have been found: 1) In phonology (al-mustawā al-ṣautī) found the use of the same final letter (qāfiyah) namely mim and using one bahr pattern namely tawil, each last stanza of this poem is harakat fathah. 2) In morphology (al-mustawā al-ṣarfī) there is shigah muballaghah. 3) In syntax (al-mustawā al-naḥwī) there is a deviation, namely taqdim wa ta'khir and ḥażaf. 4) In Semantics (al-mustawā al-dalālī) there are synonymous words and word selection according to the context of the sentence. 5) In Imagery (al-mustawā al-taṣwīrī) found the presence of majaz.